Uma proposta de integração das redes UMTS e IEEE 802.11 com suporte a mobilidade - Nogueira, Antonia Diana Braga (2007)
Wireless Local Area Networks (WLANs) IEEE 802.11 reach relatively high data transmission rates when compared to other wireless networks, such as Bluetooth. These high data transmission rates have gained attention from the cellular networks operators, which have been considering IEEE 802.11 networks as a complement to their access networks. This interoperability between cellular systems and WLANs has been frequently discussed in the literature. For example, 3GPP (Third Generation Partnership Project) has defined six levels for the complete integration of the third generation cellular networks and WLANs. However, the mobility support has not been specified yet, which is necessary to make feasible voice and data transmission transparence for the final users. Thus, this work presents two approaches for the mobility management of the integration between UMTS and IEEE 802.11 networks: the first one is based on SIP (Session Initiation Protocol), and the other one is based on MIPv6 (Mobile IP version 6). This proposal extends the Loose Interworking architecture and uses the fourth level of the 3GPP specification. First, these approaches are modeled using sequence diagrams and, then, they are mapped to the SDL (Specification and Description Language) formal description technique. SDL, which is largely used to formally specify telecommunications systems, presents simulation and validation procedures that are applied to evaluate the specification and, consequently, the proposed approaches.